2008
DOI: 10.1177/08944865080210040104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Control on the Performance and Financial Characteristics of Family Versus Nonfamily Businesses in Japan: A Matched-Pair Investigation

Abstract: Research on family businesses has undergone rapid development in the past two decades. Broadly speaking, such companies perform better than nonfamily businesses, as recent investigations in Japan support. To obtain a more precise result, this research has applied to the Japanese context a research methodology that has proven its worth in Western cases. On the basis of data covering the years 1998 and 2003, we found better performance among family businesses in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
3
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 48 publications
8
97
3
9
Order By: Relevance
“…The main challenge of family companies is to promote growth without calling into question the permanence of family control (Goffee, 1996). Such an approach is consistent with the theory of longer-term perspectives by family firms (Allouche et al, 2008). Therefore, we propose the following hypothesis:…”
Section: The Mexican Contextmentioning
confidence: 87%
See 3 more Smart Citations
“…The main challenge of family companies is to promote growth without calling into question the permanence of family control (Goffee, 1996). Such an approach is consistent with the theory of longer-term perspectives by family firms (Allouche et al, 2008). Therefore, we propose the following hypothesis:…”
Section: The Mexican Contextmentioning
confidence: 87%
“…However, a consensus definition may not represent a pertinent research goal because, by nature, family businesses are contingent on the institutional legal and cultural context, which differs from country to country (Allouche, Amann, Jaussaud, & Kurashina, 2008). Differences in institutional and cultural contexts suggest that it may be a mistake to assume that a generic definition of family firm will prevail across societies.…”
Section: Family Firmsmentioning
confidence: 96%
See 2 more Smart Citations
“…Along these lines, prior empirical research has found positive (e.g. Allouche, Amann, Jaussaud, & Kurashina, 2008;Block, Jaskiewicz, & Miller, 2011;Chu, 2009;Lindow, Stubner, & Wulf, 2010;Miralles-Marcelo, Miralles-Quirós, & Lisboa, 2014;Wagner, Block, Miller, Schwens, & Xi, 2015), negative (Cucculelli & Micucci, 2008;Sacristán-Navarro, Gómez-Ansón, & Cabeza-García, 2011), insignificant (Chrisman, Chua, & Litz, 2004;Miller, Le Breton-Miller, Lester, & Cannella, 2007;Westhead & Howorth, 2006) and even quadratic (De Massis, Kotlar, Campopiano, & Cassia, 2013;Kowalewski, Talavera, & Stetsyuk, 2010;Poutziouris, Savva, & Hadjielias, 2015) relationships between family involvement in business and firm performance. Another stream of research investigates how the specific characteristics of family business affect firm performance, especially those related to ownership, governance structure, management and succession (Block et al, 2011;De Massis et al, 2013;Garcia-Castro and Aguilera, 2014;Mazzi, 2011;Miralles-Marcelo et al, 2014;Villalonga & Amit, 2006).…”
Section: Introductionmentioning
confidence: 93%